Rastreamento do polimorfismo na enzima desiodase tipo 2 (D2) em indivíduos com síndrome de Williams-Beuren - Capra, Siriana Mansur (2016)
Williams-Beuren syndrome (WBS) is caused by microdeletions in the region 7q11.23. The main clinical features of the syndrome are congenital heart disease, typical facial dysmorphisms, friendly personality and intellectual disabilities. Previous studies have shown that polymorphism in the gene encoding the enzyme responsible for conversion of T4 to T3, the deiodinase type 2 (D2) does not alter its catalytic activity, but are positively associated with neuropsychiatric disorders and intellectual impairment, bipolar disorder and depression. Later it was demonstrated that polymorphic D2 (Thr92Ala-D2) alters the expression of genes involved in oxidative stress also altered in individuals with Alzheimer's disease. Taken together, we hipostenizamos the Thr92Ala-D2 might be related to cognitive impairment in individuals with SWB. Thus, this study aimed to track the frequency of polymorphism in a group of 63 patients with SWB and correlate the presence of the polymorphism with its indicators of intellectual functioning. Participants were 4-37 years on molecular diagnosis of SWB and were matched for sex and age. The DNA from patients was obtained from the collection of buccal epithelial cells using Swab and mutation status was determined by the technique of Polymerase Chain Reaction (PCR). Intellectual performance of participants was assessed by the instruments: WASI, WISC-III or WAIS-III. 10 individuals were identified polymorphic (A / A) and 39 heterozygotes (T / A), featuring 15.88% and 61.90% of the study population, respectively. 21 patients were evaluated and the IQ values ranged from 37 to 72, characterized intellectual deficit, mild to moderate, as described in the literature. There was no significant correlation between the presence of the polymorphism and IQ patients, even when the sample was stratified according to gender. Two patients heterozygous for the polymorphism had subclinical hypothyroidism and IQ values were 42.2 and 37. We note a full IQ downward trend as there is an increase in serum levels of TSH, although no statistical significance.